2006
DOI: 10.1523/jneurosci.3371-06.2006
|View full text |Cite
|
Sign up to set email alerts
|

Glomerulus-Specific, Long-Latency Activity in the Olfactory Bulb Granule Cell Network

Abstract: Reliable, stimulus-specific temporal patterns of action potentials have been proposed to encode information in many brain areas, perhaps most notably in the olfactory system. Analysis of such temporal coding has focused almost exclusively on excitatory neurons. Thus, the role of networks of inhibitory interneurons in establishing and maintaining this reliability is unclear. Here we use imaging of population activity in vitro to investigate the mechanisms of temporal pattern generation in mouse olfactory bulb i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
70
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(79 citation statements)
references
References 53 publications
9
70
0
Order By: Relevance
“…We found that changing the action potential train from one with uniform intervals (8 spikes at 40 ms) to one in which spikes were clustered (4 pairs of spikes at 40 ms) had no effect on the magnitude of granule cell-mediated recurrent inhibition (P > 0.8, n = 5). The lack of sensitivity to temporal coincidence of input in granule cells is consistent with the observation that they respond at long latencies 26 and are best activated by prolonged inputs 30 (see Discussion).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…We found that changing the action potential train from one with uniform intervals (8 spikes at 40 ms) to one in which spikes were clustered (4 pairs of spikes at 40 ms) had no effect on the magnitude of granule cell-mediated recurrent inhibition (P > 0.8, n = 5). The lack of sensitivity to temporal coincidence of input in granule cells is consistent with the observation that they respond at long latencies 26 and are best activated by prolonged inputs 30 (see Discussion).…”
Section: Resultssupporting
confidence: 87%
“…Previously, we have shown that granule cell calcium transients observed under these conditions are correlated with granule cell spiking 26 .…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…Such inputs have been observed from GABAergic granule cells (6,16,18) and may synchronize mitral cell firing via a mechanism dubbed "stochastic synchronization" (14). Second, we hypothesized that slow decorrelation arose from long latency, competitive recruitment of these same granule cells (11,12,42,43), giving rise to lateral inhibition whereby more active cells suppress firing of less active cells (11). We predicted that our experimental results might be explained by these known features of olfactory bulb inhibition.…”
Section: Timescale-dependent Correlation Changes In Pairs Of Active Mmentioning
confidence: 89%